2020
DOI: 10.1007/s10796-020-10043-2
|View full text |Cite
|
Sign up to set email alerts
|

Building Consumers’ Trust in Electronic Retail Platforms in the Sub-Saharan Context: an exploratory study on Drivers and Impact on Continuance Intention

Abstract: Lack of trust can have a negative influence on consumers' willingness to use electronic retail (e-tail) platforms especially in countries with weak regulations and poor consumer rights. This paper examined factors that can be employed to build consumer trust and continuance intention to use e-tail platforms in Sub-Saharan Africa. Survey data was collected from 207 respondents and analyzed using structural equation modeling with the PLS software. The results show that information quality, perceived usefulness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 68 publications
8
27
2
Order By: Relevance
“…H2 showed that website security also has a positive and significant effect on panic online buyers, but with less strength than H1. Therefore, website security is one of the key elements that considered by panic buyers when conducting e-commerce operations [58,63]. These findings align with the adaptation technology literature and behavioral reasoning theory [7,66].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…H2 showed that website security also has a positive and significant effect on panic online buyers, but with less strength than H1. Therefore, website security is one of the key elements that considered by panic buyers when conducting e-commerce operations [58,63]. These findings align with the adaptation technology literature and behavioral reasoning theory [7,66].…”
Section: Discussionsupporting
confidence: 75%
“…However, other studies reported that socially responsible consumers perceive a greater risk of buying online and confidence is lacking in the security of websites [57]. In more recent studies, researchers have found that the behaviors of socially responsible online consumers are drastically changing and relying on online shopping due to the emergence of new electronic commerce platforms, such as collaborative e-commerce, the pickup mode, and the use of social media (Facebook and WhatsApp)-online sales channels that are linked to the business website [58][59][60]. These strategies have been a key element in promoting online purchases by responsible consumers, encouraging the purchase of ecological, economical, recyclable, and sustainable products, mainly due to the social influence of communities that have already had experience with online shopping [61,62].…”
Section: Website Security and Responsible And Panic Buyersmentioning
confidence: 99%
“…The research participants were purposefully drawn from these banks because they are expected to have firsthand experience and understanding of the research problem and phenomena in the study. In each of these banks, potential research respondents with knowledge of the research area were identified (Odusanya, Aluko, and Lal, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Trust is defined as "belief that one can rely upon a promise made by another and that the other, in unforeseen circumstances, will act toward oneself with goodwill and in a benign fashion" (Suh & Han, 2003, p. 137). Trust plays an important role in internet behavior (Odusanya et al, 2020;Zhou et al, 2016). As perceived risk and uncertainty in the online environment is high, users can be suspicious about security of online commerce activities (Mulero & Adeyeye, 2013;Slade et al, 2014).…”
Section: Trustmentioning
confidence: 99%